Trigger, Self Efficacy and Motivation in The Implementation of Cervical Cancer Screening - Winarti, Eko; Santoso, Budi; Suhatno, Suhatno; Hargono, Rachmat (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Cervical cancer is currently ranked top among the various types of cancer that causes death in women in the world. The majority of women who diagnosed with cervical cancer did not do screening tests or did not follow up after abnormal results were found. The purpose of this research was to know how path analysis between motivation variable, self efficacy and trigger in the implementation of screening cervical cancer using Visual Inspection With Acetic Acid (VIA). This research used case control design. Sample size was based on the calculation of rule of the thumb. There were 410 respondents that were divided into 205 cases and 205 controls. The sample used multi stage random sampling method. The data were analyzed by using Partial Least Square - Structural Equation Modeling (PLS-SEM). There was a positive influence of trigger variable to self efficacy and motivation variable. There was positive influence of self efficacy variable toward motivation variable and the implementation of early detection of cervical cancer VIA. There was a positive influence of self efficacy variable and motivation to the execution of early detection of cervical cancer VIA. There was an indirect effect of trigger on the implementation of early detection of cervical cancer VIA. Keywords: Cervical cancer, Visual Inspection With Acetic Acid (VIA), Trigger, Self efficacy, Motivation